Cultural Competency Training of Medical Students among Trauma Patients: Training and Assessment Strategies - Shrivastava Prateek Saurabh; Mendhe Harshal G; Tiwade Yugeshwari R; Mishra Vaishnavi H (Wolters Kluwer Medknow Publications, 2024)
In the field of health care, cultural competency refers to the ability of healthcare professionals to acknowledge, respect, and accordingly respond to the varied needs, beliefs, values, and practices followed by persons and the communities they serve. The purpose of the current review is to explore the role of cultural factors and trauma experience, and identify the strategies that can be employed to train and assess medical students in cultural competency pertaining to trauma patients. An extensive search of all materials related to the topic was carried out on the PubMed and Google Scholar search engines and a total of 21 articles were selected based on their suitability with the current review objectives. Cultural factors play a defining role in determining the experiences of trauma patients, and how these patients and family members perceive, cope, and recover from such traumatic events. To meet the diverse needs of the community, the medical curriculum has to be flexible and must include the component of cultural competency. Like any other domain, medical educators must plan for the assessment of cultural competencies while delivering trauma education, as it will provide insights into the readiness of the students to deliver culturally sensitive and effective care to trauma patients. In conclusion, the inclusion of cultural competency training within trauma care in the medical curriculum carries immense utility as it can help healthcare professionals to effectively communicate and respond to the varied needs of trauma patients, regardless of their cultural backgrounds. This calls for the adoption of a combination of teaching-learning methods and assessment methods by medical educators so that medical students can be empowered to deliver culturally sensitive medical care to trauma patients.